Household food insecurity and childhood overweight in Jamaica and Québec: a gender-based analysis - Gordon-Strachan Georgiana; Girard Manon; Tatone-Tokuda Fabiola; Burnier Daniel; Francis Damion; Dubois Lise; Fox Kristin; Wilks Rainford (BMC, 2011)
Abstract Background Childhood overweight is not restricted to developed countries: a number of lower- and middle-income countries are struggling with the double burden of underweight and overweight. Another public health problem that concerns both developing and, to a lesser extent, developed countries is food insecurity. This study presents a comparative gender-based analysis of the association between household food insecurity and overweight among 10-to-11-year-old children living in the Canadian province of Québec and in the country of Jamaica. Methods Analyses were performed using data from the 2008 round of the Québec Longitudinal Study of Child Development and the Jamaica Youth Risk and Resiliency Behaviour Survey of 2007. Cross-sectional data were obtained from 1190 10-year old children in Québec and 1674 10-11-year-old children in Jamaica. Body mass index was derived using anthropometric measurements and overweight was defined using Cole's age- and sex-specific criteria. Questionnaires were used to collect data on food insecurity. The associations were examined using chi-square tests and multivariate regression models were used to estimate odds ratios (OR) and 95% confidence intervals. Results The prevalence of overweight was 26% and 11% (p < 0.001) in the Québec and Jamaican samples, respectively. In Québec, the adjusted odds ratio for being overweight was 3.03 (95% CI: 1.8-5.0) among children living in food-insecure households, in comparison to children living in food-secure households. Furthermore, girls who lived in food-insecure households had odds of 4.99 (95% CI: 2.4-10.5) for being overweight in comparison to girls who lived in food-secure households; no such differences were observed among boys. In Jamaica, children who lived in food-insecure households had significantly lower odds (OR 0.65, 95% CI: 0.4-0.9) for being overweight in comparison to children living in food-secure households. No gender differences were observed in the relationship between food-insecurity and overweight/obesity among Jamaican children. Conclusions Public health interventions which aim to stem the epidemic of overweight/obesity should consider gender differences and other family factors associated with overweight/obesity in both developed and developing countries.